Impression cytology of the ocular surface. Issue 12 (18th November 2005) - Singh, R; Joseph, A; Umapathy, T; Tint, N L; Dua, H S
Abstract : Impression cytology refers to the application of a cellulose acetate filter to the ocular surface to remove the superficial layers of the ocular surface epithelium. These cells can then be subjected to histological, immunohistological, or molecular analysis. Proper technique is essential as the number of cells sampled can vary considerably. Generally two to three layers of cells are removed in one application but deeper cells can be accessed by repeat application over the same site. Applications for impression cytology include diagnosing a wide range of ocular surface disorders, documenting sequential changes in the conjunctival and corneal surface over time, staging conjunctival squamous metaplasia, and monitoring effects of treatment. It is also a useful investigational tool for analysing ocular surface disease with immunostaining and DNA analysis. It is non-invasive, relatively easy to perform, and yields reliable information about the area sampled with minimal discomfort to the patient. Major ophthalmic centres should develop and introduce this technique into routine clinical practice. This is best achieved with a team approach including the ophthalmologist, pathologist, microbiologist, and the immunologist.